Mixed Methodological Exploratory Study Of Knowledge, Attitude And Practice Among Healthcare Practitioners On The Application Of Precision Medicine In Cancer Patients At Lahore, Pakistan - Rida, Naeem (2024)
Precision medicine (PM) is bringing revolutionary advancements allowing healthcare practitioners to treat every cancer patient according to the patient’s genetic findings. But it is relatively a new treatment approach in Pakistan. So, it is important to explore and look into the level of knowledge, attitude, and challenges faced by health practitioners for its practice in the country. A sequential exploratory mixed-method design was adopted for this purpose, comprising of a phase-I qualitative study and a phase-II quantitative study. Targeted population was oncology physicians and pharmacists working in oncology hospitals in Lahore, Pakistan.